The CURL-CoFoR Collaborative Collection Management Project - Walker, Gregory (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
CoFoR originated from an initiative by CURL, the Consortium of Research Libraries in the British Isles. CURL’s Task Force on Resource Management proposed a project, which would develop and test several interrelated aspects of collaborative collection management (CCM), to help in determining the most effective kinds of collaboration between major research collections. The Task Force was concerned that local pressures on libraries were tending to make them take collection management decisions in isolation, and they were looking for a framework within which better informed decisions on libraries’ collections could be taken with greater confidence and a clearer awareness of national provision. CURL was seeking to establish which CCM approaches could be expected to: · offer the most attractive benefits for costs incurred; · be applicable to a wide range of subjects / areas; · and be viable in the longer term. In lat 2002 CURL accepted a proposal from an existing project team to undertake this work.